Daily and school physical activity of 16 year-old girls and boys - Dorota Groffik; Karel Frömel; Marta Witek-Chabińska; Rafał Szyja; Radim Žatka; Bartosz Urbański (Health Promotion & Physical Activity, 2018)
The aim of the work was to determine the relationship between school and all-day physical activity of 16-year-old girls and boys based on weekly monitoring using pedometers. The research also took into account the level of all-day physical activity of less and more active pupils before school classes. 169 people were examined, including 93 girls and 76 boys from secondary schools of the Silesian region. The subjects wore a pedometer for 5 school days, recording the number of steps performed in individual segments of the day (time before classes at school, during classes at school and time after completing classes at school) in specially prepared tables. The research results indicated that girls are more active in terms of the number of steps taken on school days from boys. Girls and boys meet the recommendation of the school number of steps in the dimension of 3 000. However, the difference in physical activity was observed, considering the division of respondents into less and more active in time before school classes. Students who are less active in terms of the number of steps taken before the start of classes at school do not meet the recommended school recommendation of physical activity. It is necessary to look for reserves of physical activity throughout the day. In addition to physical education lessons, the school should promote activity during breaks, mid-term exercises or encourage active locomotion before and after school classes. Encouraging an increased number of walks, active transport to/from school, cycling, roller skating among children and adolescents is an important element in the preparation for lifelong activity and a healthy lifestyle.